BOKO HARAM: A 21st CENTURY CHALLENGE IN NIGERIA - Ahokegh, A. F. (European Scientific Journal, ESJ, 2012)
Though, Nigeria has ever faced series of security threatening challenges, the one caused by the activities of the Islamist sect, the Boko Haram remains quite unique in all ramifications. For instance, the Jos crises that claimed dozens of human lives were known to be limited to Plateau State and so also were the Niger Delta crises limited to the areas of the creeks of the River Niger. The sect claims responsibility for several bombings and snip activities in the northern and central Nigeria, thereby placing the nation at the threshold of disintegration. The central issue of this paper is to probe into the causes of the Boko Haram menace and why government has been unable to put an end to it. The author sees Boko Haram as an outcome of Nigeria‟s internal political, social, economic and to some extent, religious problems. It is therefore concluded with a position that the present happenings in Nigeria have undoubtedly made the call for a national conference very obvious. This will provide the platform for discussing grievances of groups for amicable solutions.